Control Economical Soybean Raw Material Inventory Control Using EOQ and POQ Methods (Case Study: Abdul Tofu Factory) - Syarif, Abdul Azis; Utama, Denny Walady; Ramadhan, Surya (PT. SAFARI AMALIA, 2024)
Every company in the industrial sector, whether large, medium or small, requires effective raw material inventory control to ensure operational continuity and reducse costs. Mr. Abdul’s Tofu Factory, an example of an UMKM that was founded in 2011, produces tofu with the main raw material being soybeans (Glycine max), which has high demain the market. However, the processing of soybean raw material supplies at this factory is not yet optimal, characterized by excess stock which results in increased costs and unplanned purchases of raw materials. This research aims to analyze inventory control of soybean raw materials using the Economic Order Quantity (EOQ) and Periodic Order Quantity (POQ) methods to determine the most economical order quantity. Data one the Purchase and use of soybeans at Mr Abdul’s Tofu Factory in the period January-December 2022 was analyzed. The research results show what the POQ method is more efficient than EOQ, with an optimal order quantity of 2.514,40 kg and frequency of purchases twice a year. The POQ method is able to produce total inventory costs of IDR 3.788.290,55, lower than other methods. Therefore,the application of the POQ method is recommended to minimize inventory costs at Mr Abdul’s Tofu Factory and increase operational efficiency.